(3eDSSGJ GdeLJeY GdeOfj h OhQgG aj GdMjGI GdSjGSjI GdeUQjI (B/ s - (3eMeO QSJe MSjf QSJes; (3KQhJ HOhj s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2012)
(3fGbTJ gPg GdQSGdI eDSSGJ GdeLJeY GdeOfj h OhQgG aj GdMjGI GdSjGSjI GdeUQjI(B: (3MjK JYQVJ dJYQja GdeLJeY GdeOfj(B: (3h VHW eOdhdg(B: (3h HjGf NUGFUg(B: (3h eOi GSJbdGdjJg Yf GdOhdI(B: (3h cPdc GdCWQ GdCSGSjI dJaYjd OhQ eDSSGJ GdeLJeY GdeOfj dci jbhe HhXGFag Ydi Cced hLg(B: (3ceG JfGhdJ GdQSGdI echfGJ GdeLJeY GdeOfj ef GMRGH SjGSjI h LeYjGJ CgdjI h fbGHGJ egfjI h YeGdjI(B: (3ehVMI dOhQgG GdSjGSj aj OYe KbGaI Mbhb GdEfSGf h GdOaGY YfgG h OYe bje GdehGWfI(B: (3cPdc GdOhQ GdPj jfHZj Cf JdYHg eDSSGJ GdeLJeY GdeOfj aj eQMdI GdJMhd GdOjebQGWjs
(3jTJed Ydi edGMb(B: (3UaMI (B392-412s
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdYGe, (B2012s
(3jTJed Ydj EQLGYGJ HdjhLQGajI(B: (3UaMI (B369-390s
(3GdfU HGdYQHjI hGdedNU HGddZI GdEfLdjRjI hGdYQHjI(B.s
Keywords: (3GdbGfhf GdYGes; (3GdCMRGH GdSjGSjIs; (3GdLeYjGJ GdCgdjIs; (3GdeLJeY GdeOfjs; (3GdfbGHGJs; (3Mbhb GdGfSGfs; (3GdehGWfIs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdYGes